IMPLIKATUR BERDASARKAN PELANGGARAN MAKSIM DALAM KOMIK YOTSUBA&! KARYA KIYOHIKO AZUMA (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This research aimed to know and analyze implicatures utterance based on the violation of maxims in Yotsuba&! by Kiyohiko Azuma. This research is qualitative descriptive with analyzed by using contextual method. The data in Yotsuba&! were collected by using listening method and note-taking technique. As a result of the study it is found that there are as many as 20 violation of maxims and as many as 24 implicature data. In this research, only conventional implicatures are not based on cooperative principle.Key Word: implicature, maxim, comic